From Vibes to Purchase: The Emotional Bridge Between Promotion, Atmosphere, and Impulse Shopping - Muhammad Ananda Fathorozi; Amin Mansur (Marketing and Business Strategy, 2026)
This study examines the effect of Promotion and Store Atmosphere on Impulsive Buying with Positive Emotions as a mediating variable. Using a quantitative, associative approach, data were collected from 100 Lion Superindo consumers via purposive sampling and analyzed using Partial Least Squares (PLS-SEM). The findings show that Promotion and Store Atmosphere have a positive and significant effect on Positive Emotions. Promotion does not directly influence Impulsive Buying, whereas Store Atmosphere has a positive, significant effect on it. Furthermore, Positive Emotions significantly mediate the relationship between Promotion and Impulsive Buying, but not between Store Atmosphere and Impulsive Buying. The R-square value indicates moderate explanatory power, suggesting that other external factors may also influence the model. Managerially, retail managers should enhance promotional strategies that evoke positive emotions and design store atmospheres that improve customer comfort to stimulate spontaneous purchasing behavior. These results highlight the importance of emotional factors in bridging marketing stimuli and consumer impulsive buying behavior, providing strategic insights for retailers to improve customer engagement and sales performance.